A meta-analysis of biochar application to manage plant diseases caused by bacterial pathogens (Bioscience Journal, 2023)
The current agricultural scenario faces diverse challenges, among which phytosanitary issues are crucial. Plant diseases are mostly treated with chemicals, which cause environmental pollution and pathogen resistance. In light of the UN Sustainable Development Goals (SDGs), the biochar alternative use to chemical inputs fits into at least six of the proposed goals (2, 3, 7, 13, 15, and 17), highlighting the 12th, which explains responsible consumption and production. Biochar is valuable for inducing systemic resistance in plants because it is a practical and frequently used resource for improving physical, chemical, and biological soil attributes. This review assessed the beneficial and potential effects of applying biochar to agricultural soils on bacterial pathogen management. Such application is a recent strategy; therefore, this research evaluated 20 studies that used biochar to manage plant diseases caused by pathogens inhabiting the soil in different systems. The effectiveness of biochar application in controlling plant diseases has been attributed to its alkaline pH, which contributes to the growth of beneficial microorganisms and increases nutrient availability, and its porous structure, which provides habitat and protection for soil microbiome development. Therefore, the combined effect of improvements on soil attributes through biochar application aids pathogen control. Biochar application helps manage plant diseases through different mechanisms, inducing plant resistance, increasing activities and abundance of beneficial microorganisms, and changing soil quality for nutrient availability and abiotic conditions.